Quality and Flavor Profiles of Arabica Coffee Processed by Some Fermentation Treatments: Temperature, Containers, and Fermentation Agents Addition - Yusianto .; Sukrisno Widyotomo (Indonesian Coffee and Cocoa Research Institute, 2013)
Coffee fermentation is a step of wet processing. In fact, some microorganisms naturally exist on the surface of coffee cherry. Using a starter culture of microorganisms may change equilibrium of microorganism population. Among some safe fermentation agents are present in “ragi tape” (yeast), “ragi tempe”, and fermented milk. A fermentor machine equipped with eating-control and stirrer had been designed, and tested before. Some treatments investigated were fermentation containers (fermentor machine and plastic sacks); fermentation agents (fresh cage-luwakcoffee, “ragi tape”, “ragi tempe”, and fermented milk); temperature of fermentation (room, 30 C, 35 C, and 40 C); and duration of fermentation (6, 12, and 18 hours). The experiment were replicated three times. Wet-coffee parchments were washed and sundried until moisture content reached 12%. The dried parchment was hulled and examined for the bean quality and flavors. The experiment indicated that 40 C fermentation in fermentor machine resulted in higher content of “full sour defect”. Fermentation agents significanly influenced bean size. Temperature treatment significanly influenced bulk density and bean size. The best flavor profile was obtained from fermentation in plastic sack at ambient temperature. Bacteria of fermented milk and “fresh luwak coffee” as fermentation agents resulted up to excellent flavor. Twelve hours fermentation produced best flavor of Arabica coffee compared to 6 and 18 hours. Key words: Arabica coffee, fermentation, flavour, fermentation agents